Kontekstualisme - Fra modernistisk metode til post-analytisk historicisme? - Bevir, Mark (Slagmark - Tidsskrift for idéhistorie, 2018)
This article provides a critical history of the Cambridge School of intellectual history. Laslett’s work on Locke appeared to vindicate modernist historicism. Laslett shunned the broad narratives of romantic developmental historicists. He relied on bibliographies, unpublished manuscripts, and other evidence to establish atomized facts and thus textual interpretations. Pocock and Skinner’s theories defended modernist historicism. They argued historians should situate texts in contexts and prove interpretations correct by using modernist methods to establish empirical facts. They attacked approaches that read authors as contributing to perennial debates or aiming at a coherent metaphysics. I argue we should reject modernist historicism with its methodological focus; we should adopt a post-analytic historicism focused on philosophical issues arising from analyses of the human sciences as studying actions by attributing meanings to actors and showing how these meanings fit into larger webs of belief.